Campylobacter jejuni ST353 and ST464 cause localized gut inflammation, crypt damage, and extraintestinal spread during large- and small-scale infection in broiler chickens - Heather Chick (Applied and Environmental Microbiology, 2025)
Campylobacter infections in humans and chickens are a significant burden to health services and the poultry industry. In the UK, over 75% of chicken products are Campylobacter-positive at retail, but the knowledge of the mechanisms responsible for extraintestinal spread into edible tissues remains incomplete. This work aimed to establish if two chicken-associated lineages of Campylobacter jejuni, ST353 and ST464, have the potential for extraintestinal spread. Large- and small-scale chicken colonization trials investigated the infection biology of C. jejuni ST353 (three strains) and ST464 (four strains). Both lineages strongly colonized the ileum and ceca and were detected in liver and spleen. C. jejuni ST353 and ST464 spleen load were significantly increased compared to C. jejuni M1 controls. Immune responses in cecal tonsils exhibited early induction of IFN-γ and suppressed TGFβ at 7 days post-infection with C. jejuni ST464. Histochemistry of gut tissue demonstrated significant decreases in intestinal crypt depth in ileal tissue with increasing severity relative to Campylobacter lineage, M1 <ST353<ST464. Pairwise correlation analysis confirmed strong interdependencies between “cecal Campylobacter load,” “CXCLi1,” “CXCLi2,” and “splenic Campylobacter load.” Furthermore, linear discriminant analysis confirmed that cecal tonsil-derived IFNγ, TGFβ, and CXCLi1 could predict splenic invasion at 71% accuracy. This work demonstrates that two chicken specialist C. jejuni lineages, ST353 and ST464, cause extraintestinal spread to liver and spleen and modeling suggests distinct routes from ileum and cecum, respectively. Recognition of these two routes of Campylobacter extraintestinal spread (ileal/liver and cecal/spleen) provides a better understanding of this food-derived pathogen for academia and the industry.